Increase of prognostic possibilities of the IQ tests used in professional selection to the higher military educational establishments of the Ministry of Internal Affairs, Ukraine - Matsegora, Ya. V. (Honor and Law, 2019)
Modern researches on interrelation of personality traits with intelligence are considered. Data of empirical research of interrelation of intelligence with the character accentuation of cadets of the Academy of the Interior Troops of the Ministry of Internal Affairs, Ukraine, with different training results are given.